Statistical theories and methods: a panacea for identifying the cause of low political participation among statisticians towards enhanced national development - Omebo, D.M.O.; Emmanuel†, A.Y; Ailobhio‡§, T.D; Hassan††‡‡, A.A. (International Journal of Mathematical Analysis and Modelling, 2023)
The desire of every citizen of a nation is to have overall development. This can only be achieved through implementation of government policies and programmes which are offshoot of research results. In most cases, persons found on the corridors of power neglect results of this research which is the bedrock of development. This paper made use of statistical theories and methods to ascertain if the claim in some quarters that the poor performance of statistics students in political and social sciences related courses is the cause of the political apathy among statisticians which has paved the way for people who have no regard or importance of research which is the walk path to sustainable development to dominate the political space. An analysis of variance for categorical data (catanova) was used in carrying out the test. The statistical findings were based on the result of GST211 (politics, peace studies and conflict resolution) course of students of department of statistics, computer science and agricultural economics of the Federal University of Lafia, Nasarawa state, Nigeria. It was discovered that students of the department of statistics performed worst among the three departments that took the course thereby justifying the claim that poor performance in political and social science related courses is the cause of political apathy among statisticians. The researchers therefore recommend for aggressive enlightenment by lecturers of the department of statistics among their students on the need to develop high interest in political and social science related courses so as to increase political participation of statisticians in order to bring more statistician to the corridor of power for the implementation of the research results rather than turning out research results that are never implemented.